The Memoirs of John Addington Symonds A Critical Edition - Regis, Amber K.; SpringerLink (Online service) (London : Palgrave Macmillan UK(Imprint), 2016)
This edition is the first to reproduce John Addington Symonds's Memoirs in its entirety. It offers a panoramic view of middle-class Victorian life, shedding light upon sexual cultures and life histories too often hidden from history. Symonds (1840-93) began writing his Memoirs in 1889. It was, he confessed, 'a foolish thing to do.' Symonds was a respected man of letters, an historian, translator, essayist and poet; he was also married with children. But rather than unfold a simple tale of public and private achievement, the Memoirs record his struggle to reconcile his homosexuality with these professional and familial identities. His autobiography offers a confessional account of relationships beyond the accepted bounds of nineteenth-century social mores, presenting an alternative case study that contests the legal and medical authorities that would label his desires a crime or disease. Yet being so eloquent on matters of heterodox sexuality, the Memoirs were suppressed. The manuscript survives because Symonds recognised its import, however 'foolish': he instructed his literary executor to preserve the text, a duty ultimately discharged by placing the manuscript under embargo in the care of the London Library.
Contents -- Acknowledgements -- List of Figures -- List of Tables -- Introduction -- Notes on the Text -- The Memoirs of John Addington Symonds -- Appendix 1: Miscellaneous papers bound with the Memoirs manuscript -- Appendix 2: Letters bound with Chapter 16 -- Appendix 3: Rewritten pages (MS 517a-b) -- Index .
Keywords: Literature, Modern-19th century; Europe-History-1492-.; Literature-History and criticism; Sociology; History of Britain and Ireland; Gender Studies